Multi-Omics Uncover Neonatal Cecal Cell Development Potentials - Chen, Liang; Meng, Qingshi; Li, Shen; Jiang, Yue; Zhang, Cong; Tang, Shanlong; Zhong, Ruqing; Tang, Xiangfang; Zhang, Sheng; Feng, Xiaohui; Zhao, Yong; Zhang, Hongfu (Frontiers in Cell and Developmental Biology, 2022)
Although, the cecum plays vital roles in absorption of water, electrolytes, and other small molecules, and harbors trillions of commensal bacteria to shape large intestine immune functions, it is unknown the cecum development potentials at single cell level during the very crucial neonatal developmental period. Using singe cell RNA-seq and proteomics, we have characterized six major types of cecal cells: undifferentiated cells; immune cells (Ims); cecumocytes (CCs); goblet, Paneth like cells (PLCs), and enteroendocrine cells (EECs) with specific markers. CCs mature with a gradual decrease in number; however, Ims develop with a continuing increase in number. Meanwhile, goblet and EEC cells reduced in number from do to d14 or d21; PLCs increased in number from d0 to d7 then decreased at d14 and d21. The cells exhibit specific development and maturation trends controlled by transcriptional factors, ligand-receptor pairs, and other factors. As piglets grow, cecal content and mucosal microbial diversity increases dramatically with population of beneficial microbiota, such as lactobacillus. Moreover, cecal mucosal-associated and cecal content microbiota are positively correlated and both show significant correlation with different types of cecal cells and plasma metabolites. This is the first presentation of neonatal cecal cell development and maturation naturally at single cell level with transcript, protein, microbiota and metabolism perspectives. Furthermore, this study provides an important tool for the determination of novel interventions in cecal drug delivery and metabolism studies.